OPERATION OF MOSUL – DOKAN RESERVOIRS AND SAMARRA BARRAGE USING HEC – RES.SIM MODEL DURING FLOOD PERIOD - Thabet M.Abdulateef; Raad Hoobi; Ali Sadeq Abbas (Journal of Engineering and Sustainable Development, 2022)
Major dams on Tigris River were designed and constructed as multi – purposes reservoirs. Since the flood event may occur for a specified period of the year, simulation model could be developed for rapid release decision according to time series reservoir inflow. This study deals with the application of HEC – ResSim version 3.1 in order to simulate and evaluate the behavior of the reservoirs system represented by Mosul, Dokan reservoirs, and Samarra barrage during the flood period 1987-1988 which is considered as a flood period. The release function of date was applied as an operating rule in order to provide safety reservoir storage accompanied with downstream release control. The results obtained from simulation of operating alternatives had been compared with the historical recorded data for the same time of simulation period, and exhibit flood control caused by specifying reservoir outflow with an appropriate limits yields appreciable matching between reservoirs' rule curves and computed pool elevation for both reservoirs. The simulation plots revel the ability of the existing projects to assist in sizing flood risk during flood event, and the storage level in the reservoirs reached a suitable elevation according to the time period of inflow, storage, and release values with the ability of Samarra barrage to divert excess flood water towered Tharthar Lake.